PARTISIPASI MASYARAKAT PESISIR DALAM MENGEMBANGKAN DESTINASI WISATA PANTAI DI DESA CAMPLONG KABUPATEN SAMPANG - Imadoeddin Imadoeddin; Syaiful Anam; Rini Aristin; Hasbullah Hasbullah; Mohammad Rudiyanto (KOLONI, 2022)
Camplong Beach is a tourist attraction with a strategic location and the most crowded of visitors. However, lately the number of visitors has decreased due to Camplong beach which is no longer in demand by the public, especially the coastal community and visitors because some of the tourist attractions are not maintained, there is garbage scattered on the beach, and the lack of amusement rides. Speaking of tourism, competition is currently tight. All tours are vying to attract visitors. Why in the world of tourism, competition is fierce, because tourism is now a pillar of the Indonesian economy after trade. The current growth of the tourism sector can provide benefits for both the State and the surrounding community. One example is the growth of the economy and the availability of jobs. This study uses the Community Participation Theory from Keith Devis, among others: (1) participation or participation (involvement / participation); (2) the availability of making a contribution to efforts in achieving group goals, this means a sense of pleasure, volunteerism in helping the group, a person becomes a member of the group with all its values; (3) the element of responsibility, this element is a prominent aspect of the feeling of being a member. Based on the results of the research conducted, there are three important elements in Keith Devis' definition of participation, namely participation, availability to contribute, and responsibility. Using the participation theory, it resulted that community participation was very enthusiastic, the availability of community contributions in developing destinations was still considered sufficient, and community responsibility was still relatively low. From this research, community participation in developing coastal tourist destinations in Camplong Village, Sampang Regency is still low, especially in the element of responsibility which has been stated by Keith Devis. Keywords: Coastal Community Participation, Tourism Destinations